Risk factors associated with malaria infection in children aged from 6 to 59 months in Niger: a cross-sectional study - N’Kpingou Théodore Nadakou; Moussiliou Noel Paraïso; Jean Blaise Yobo; Charles Patrick Makoutode; Joel Sodjinou; Ounoussa Tapha; Éric Omar Adehossi (BMC Public Health)
Abstract Background Malaria is a pathology that contributes significantly to the increase in infant and child mortality and is ranked as the second leading cause of mortality after HIV/AIDS in Africa. WHO has recommended seasonal malaria chemoprevention to fight this pathology effectively. However, it is clear that the under-5 age group remains and continues to have one of the highest mortality rates due to malaria. With this in mind, we conducted this study on the prevalence and risk factors associated with malaria infection in children aged 6–59 months in Niger, and consequently to help inform national malaria control programs on how best to use their resources to achieve their objectives. Methods To achieve the objective of this study, we first used the database of the Niger Malaria Indicator Survey (MIS). It was carried out in 2021 by the National Institute of Statistics (NIS) in collaboration with the National Malaria Control Program (NMCP) of the Ministry of Public Health, Population and Social Affairs (MSP/P/AS). Secondly, we used the databases of Notifiable Diseases (DND) of the Directorate of Surveillance and Response to Epidemics (DSRE) of Niger from 2019 to 2022. Results Of the children who received a Rapid Diagnostic Test (RDT), 23.70% were positive for malaria in 2021 in Niger. The standard of living of households, the highest level of education of the mother, the place of residence, and the child’s sex all influence the probability of children having malaria. Children from low-income households and those from middle-income households are respectively 50% and 63.7% more likely to have malaria compared to those from high-income households. Children whose mothers have no level of education and those whose mothers have a primary level of education have a risk respectively 2.5 times and 2.3 times greater of having malaria than those whose mothers have the highest level. Children in urban areas are 69.1% less likely to suffer from malaria infection than those in rural areas. Conclusion The results suggest that improving the standard of living and education of mothers could reduce malaria infection rates among children. Malaria is much more prevalent in rural areas.